Genome-wide identification and characterization of CONSTANS-like gene family in radish (Raphanus sativus). - Tianhua Hu; Qingzhen Wei; Wuhong Wang; Haijiao Hu; Weihai Mao; Qinmei Zhu; Chonglai Bao (PLoS ONE, 2018)
Floral induction that initiates bolting and flowering is crucial for reproductive fitness in radishes. CONSTANS-like (CO-like, COL) genes play an important role in the circadian clock, which ensures regular development through complicated time-keeping mechanisms. However, the specific biological and functional roles of each COL transcription factor gene in the radish remain unknown. In this study, we performed a genome-wide identification of COL genes in the radish genome of three cultivars including 'Aokubi', 'kazusa' and 'WK10039', and we analyzed their exon-intron structure, gene phylogeny and synteny, and expression levels in different tissues. The bioinformatics analysis identified 20 COL transcription factors in the radish genome, which were divided into three subgroups (Group I to Group III). RsaCOL-09 and RsaCOL-12 might be tandem duplicated genes, whereas the others may have resulted from segmental duplication. The Ka/Ks ratio indicated that all the COL genes in radish, Arabidopsis, Brassica rapa, Brassica oleracea, Capsella rubella and rice were under purifying selection. We identified 6 orthologous and 19 co-orthologous COL gene pairs between the radish and Arabidopsis, and we constructed an interaction network among these gene pairs. The expression values for each COL gene during vegetable and flower development showed that the majority of Group I members had similar expression patterns. In general, the expression of radish COL genes in Groups I and III decreased during development, whereas the expression of radish COL genes in Group II first increased and then decreased. Substantial numbers of radish COL genes were differentially expressed after vernalization treatment. The expression levels of RsaCOL-02 and RsaCOL-04 were significantly increased during vernalization treatment, while the expression of RsaCOL-10 was significantly decreased. These outcomes provide insights for improving the genetic control of bolting and flowering in radish and other root vegetable crops, and they facilitate genetic improvements to radish yields and quality.